1997
DOI: 10.1046/j.1537-2995.1997.37197176945.x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of p‐selectin during collection, processing, and storage of platelet concentrates: relationship to loss of in vivo viability

Abstract: These studies show that p-selectin expression on the platelet surface is a predictor of platelet viability, although the extent of shape change and the hypotonic shock response may be more sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
193
4
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(224 citation statements)
references
References 28 publications
22
193
4
5
Order By: Relevance
“…Surface expression of GPIIb/IIIa, Pselectin and GPIb can be measured by flow cytometry. Increased P-selectin expression during storage has been reported by several authors [15][16][17] whereas GPIb has been shown to decrease during storage [15,17]. It is however unclear whether the level of in vitro platelet activation in stored PCs correlates with in vivo survival and haemostatic function of platelets after transfusion [18].…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Surface expression of GPIIb/IIIa, Pselectin and GPIb can be measured by flow cytometry. Increased P-selectin expression during storage has been reported by several authors [15][16][17] whereas GPIb has been shown to decrease during storage [15,17]. It is however unclear whether the level of in vitro platelet activation in stored PCs correlates with in vivo survival and haemostatic function of platelets after transfusion [18].…”
Section: Flow Cytometrymentioning
confidence: 99%
“…The studies suggested that the degree of in vitro activation as evidenced by the expression of CD63 and Annexin 142+10 149+12 165+15 223+12▲ 129+9 134+14 142+12 149+10▲ 119+10 121+10 130+10 139+12▲ ▲Significant difference between BC, PC and APC; Values are mean+standard deviation; n=25. [2,4,12,14].…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that in addition to pH, volume and cell counts; in vitro platelet activation markers were used to monitor platelet [3,13,14]. These data suggest that measurement of CD63, Annexin V and LDH may be a more desirable markers for clinical studies of activated platelets, since it may be less susceptible to artifactual elevation due to minor variations in sample handling and assay [3,12,14]. The results of this study showed that the LDH levels were also increased during storage in platelet concentrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets processed by the buffy coat technique showed less p-selectin (CD62P) expression than platelets prepared by the PRP method. This study shows that in addition to pH and cell counts; in vitro platelet activation markers were used to monitor platelet quality [11,19]. These data suggest that measurement of CD62P and Annexin V may be a more desirable marker for clinical studies of activated platelets, since it may be less susceptible to artifactual elevation due to minor variations in sample handling and assay procedures [13][14][15].…”
Section: Discussionmentioning
confidence: 99%